The Role of Consumer Trust in Mediating the Effect of Service Quality on Medicine Purchase Decisions at Pangkalan Pharmacy (Pusat Riset dan Inovasi Nasional, 2025)
Increasing competition among pharmacies requires each pharmacy not only to provide a complete range of pharmaceutical products but also to deliver high-quality services and build consumer trust. This study aims to analyze the effect of service quality on drug purchase decisions, with consumer trust acting as a mediating variable at Apotek Pangkalan in Cirebon Regency. This research employs a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 315 consumers of Apotek Pangkalan who had purchased medicines at least once. The results indicate that service quality has a positive and significant effect on drug purchase decisions. Service quality also has a positive and significant effect on consumer trust. Furthermore, consumer trust is proven to have a positive and significant effect on drug purchase decisions. The results of the indirect effect analysis show that consumer trust is able to mediate the relationship between service quality and drug purchase decisions at Apotek Pangkalan. This study concludes that improving pharmacy service quality not only directly encourages purchase decisions but also strengthens consumer trust, which in turn enhances drug purchase decisions.